(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This thesis examines the concept of the Aryans paradigm through historical, linguistic, and archaeological lenses. It explores the origins, migrations, and cultural influence of Indo-Iranian groups, commonly referred to as Aryans, across Central and South Asia. By integrating archaeological evidence from the Bactria–Margiana Archaeological Complex (BMAC) and linguistic data from Proto-Indo-Iranian languages, this research investigates the interactions between migrating Aryan groups and established local civilizations. The study emphasizes the complexities of defining Aryans in terms of ethnicity, language, and socio-cultural impact and highlights the significance of an interdisciplinary approach for reconstructing early Indo-European history.